Characteristics And Knowledge of Mothers about Stunting Who Have Toddlers with Stunting - Aticeh Aticeh; Gita Nirmala Sari; Silvia Sandra Lolita (Women, Midwives and Midwifery, 2023)
Background: The prevalence of stunted toddlers is around 24.4%. Meanwhile, in 2022, the results of the Indonesian Nutrition Status Survey (SSGI) prevalence of toddlers with stunting will decrease to 21.6%, a decline of 2.8% from 2021 Purpose: This study aims to assess the association between the characteristics and knowledge about stunting of mothers who have toddlers and the incidence of stunting Methods: The research design used is quantitative, with an analytical survey design using a selective cross-sectional approach. The sample comprises 98 respondents’ mothers with children under five and their toddlers. The data collection instrument used was a questionnaire. Statistical analysis used Chi-square. Results: There is an association between the mother's age, education, family income, and knowledge with the incidence of stunting in children under five years. Conclusion: A mother's characteristics and knowledge are closely related to the incidence of stunting. It is essential to provide education for mothers to prevent stunting in children.